The Role of Using Digital Technology in the Competitiveness of MSMEs in Makassar - Andi Tenri Ampa (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to quantitatively examine the role of the use of digital technology in increasing the competitiveness of MSMEs in the city of Makassar. Through a quantitative approach, this research will analyze the relationship between the use of digital technology, management skills and the competitiveness of MSMEs in Makassar. The research sample will involve MSMEs in various sectors in the city of Makassar. Data will be collected through a survey using a questionnaire filled out by MSME owners or managers. The collected data will be analyzed using statistical techniques to identify the relationship and influence of the variables studied. Meanwhile, the sampling method uses a porpusive sampling technique. The sample in this research was 35 respondents, so that this research could be successful and produce quality research results. In order for this research to provide good research results, a research instrument test was carried out. The instrument tests used are validity tests and reliability tests. Hypothesis tests were also carried out, namely normality tests, multicollinearity tests, and multiple linear regression analysis